2014
DOI: 10.1111/bph.12861
|View full text |Cite
|
Sign up to set email alerts
|

The neurosteroid 5β‐pregnan‐3α‐ol‐20‐one enhances actions of etomidate as a positive allosteric modulator of α1β2γ2L GABAA receptors

Abstract: BACKGROUND AND PURPOSENeurosteroids potentiate responses of the GABAA receptor to the endogenous agonist GABA. Here, we examined the ability of neurosteroids to potentiate responses to the allosteric activators etomidate, pentobarbital and propofol. EXPERIMENTAL APPROACHElectrophysiological assays were conducted on rat α1β2γ2L GABAA receptors expressed in HEK 293 cells. The sedative activity of etomidate was studied in Xenopus tadpoles and mice. Effects of neurosteroids on etomidate-elicited inhibition of cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 53 publications
6
16
1
Order By: Relevance
“…Interestingly, the addition of 10-1000 nM alphaxalone to the combination of 0.5 mM GABA 1 1 mM propofol did not lead to further enhancement of steady-state current. This is in contrast to our recent finding that neuroactive steroids can potentiate peak currents elicited by a combination of GABA and an allosteric activator (Li et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the addition of 10-1000 nM alphaxalone to the combination of 0.5 mM GABA 1 1 mM propofol did not lead to further enhancement of steady-state current. This is in contrast to our recent finding that neuroactive steroids can potentiate peak currents elicited by a combination of GABA and an allosteric activator (Li et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
“…For example, we estimate that the half-maximal concentration of etomidate producing an increase of steady-state currents is 0.9 mM (Fig. 3A), whereas our recent study on the effect of etomidate on peak currents from a1b2g2L receptors revealed an EC 50 of 2 mM (Li et al, 2014). Similarly, while the EC 50 for potentiation of steady-state currents by propofol was 0.4 mM (Fig.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This result indicates that these steroid anesthetics do not compete for the binding to the intersubunit sites we recently located at the extracellular end of the transmembrane domain at the β + –α − (etomidate 28 ) and at the α + – β − and γ + –β − subunit interfaces (barbiturate). 22 This result is also consistent with the earlier ones showing an enhancement of anesthetic potency of etomidate by neurosteroids 35 and of chromaffin cell‘s responses to natural neurosteroids in the presence of a variety of barbiturates. 36 Our results confirm that these sites (etomidate, barbiturate and neurosteroid) are nonidentical, but their occupancies are allosterically coupled.…”
Section: Discussionsupporting
confidence: 91%
“…[35] When administered together, neurosteroids and anesthetic agents can enhance GABA A receptor-mediated inhibition in a synergistic manner. [36] This finding suggests that the combined use of anesthetics and neurosteroids may significantly reduce dose requirements needed for clinical anesthesia, which in turn should reduce cardiovascular and respiratory side effects.…”
Section: Neurosteroid Analogues For Providing Anesthesiamentioning
confidence: 99%